Frequency Comb Effect on Chaos in Semiconductor Lasers, a Bifurcation Study - Najm M. Al-Hosiny (International Journal of Optics)
This study investigates the effects of optical frequency comb injection on the chaotic dynamics of semiconductor lasers through a bifurcation analysis. By examining the behavior of semiconductor lasers under different comb parameters (i.e., the number of signals, comb spacing), the research explores how these factors influence the system’s transition from stable and periodic to chaotic regimes. Bifurcation diagrams for both 3-signal and 5-signal combs reveal complex nonlinear patterns, especially with varying frequency detuning and injection strength. The findings show that increasing the number of signals and comb spacing intensifies the nonlinear interactions, leading to faster transitions to chaos and richer dynamical states. Increasing comb spacing has also shown to enhance periodicity of the system regardless of the number of signals. This study provides insights into the routes to chaos in optically injected semiconductor lasers and highlights the potential of frequency comb manipulation for controlling chaos, with applications in secure communication, high-speed signal processing, and dual-comb spectroscopy.